Microstructure and corrosion behavior of Y-modified ZK60 Mg alloy prepared by laser powder bed fusion. (February 2023) - Liang, Jingwei; Wu, Shibo; Li, Bingwei; Lei, Zhenglong; Chen, Yanbin; Jiang, Meng; Zhang, Xinrui; Chen, Xi
Abstract: The microstructure and corrosion behavior of Y-modified ZK60 Mg alloy prepared by laser powder bed fusion (LPBF) are studied. By controlling the content of Y, the quantity, distribution, and type of precipitates are regulated, and the corrosion resistance is improved. Specifically, the ZK60 alloy with 1 wt% Y exhibits excellent corrosion resistance, which is mainly due to the formation of a continuous network of rare earth-containing precipitates at the grain boundaries that form corrosion barriers to impede corrosion and induce grain refinement. In addition, the passivation and stability of the surface film are improved after the addition of Y. Highlights: The microstructure and corrosion behavior of LPBF-processed ZK60- x Y are studied. The LPBF-processed ZK60-1Y alloy exhibits excellent corrosion resistance. Continuous rare-earth precipitates at grain boundaries form corrosion barriers. The microcracks are suppressed after adding an appropriate amount of Y.